Interaction of electrolyte molecules with carbon materials of well-defined porosity: Characterization by solid-state NMR spectroscopy - Borchardt, Lars; Oschatz, Martin; Paasch, Silvia; Kaskel, Stefan; Brunner, Eike (Physical Chemistry Chemical Physics, 2013)
Electrochemical double-layer capacitors (EDLCs or supercapacitors) are of special potential interest with respect to energy storage. Nearly all EDLCs make use of porous carbons as electrode materials. Further tuning of their performance in EDLC applications requires a better understanding of their properties. In particular, the understanding of the interactions between carbon-based materials and electrolyte solutions is of fundamental interest with respect to future applications. Since the capacitance of carbon-based electrode materials is known to depend on the pore size, we have studied different porous carbon materials of well-defined, variable pore size loaded with 1 M TEABF 4 in acetonitrile or with pure acetonitrile using solid-state magic angle spinning (MAS) 1H, 11B, and 13C NMR spectroscopy. © the Owner Societies 2013.
CRIS-Team Scopus Importer:2023-03-20